Sex steroid hormones: an overlooked yet fundamental factor in oral homeostasis in humans - Cornejo Ulloa, Pilar E.; Krom, B. P.; Schoonmade, Linda J.; van der Veen, M. H. (Frontiers in Endocrinology, 2024)
Sex steroid hormones (SSH) are extremely versatile molecules with a myriad of physiological functions. Next to their well-known role in sexual development and reproduction, SSH play active roles in practically every tissue in the human body, including the oral cavity. It has long been demonstrated that periodontal tissues express SSH receptors and therefore are responsive to the presence of SSH. Interestingly, SSH not only interact with the periodontal tissues but also with other tissues in the oral cavity such as dental enamel, pulp, cementum, oral mucosa, and salivary glands. Questions concerning the possible physiological functions of these receptors and their role in maintenance of oral health, remain unanswered. The purpose of this scoping review was to gather and summarize all the available evidence on the role of SSH in physiological processes in the oral cavity in humans. Two comprehensive literature searches were performed. References were screened and selected based on title, abstract and full text according to our inclusion criteria. Both searches yielded 18,992 results of which 73 were included. Results were divided into four categories: (1) Periodontium;(2) Dental structure; (3) Mucosa; and (4) Salivary glands. The interaction of these tissues with progestagens, androgens and estrogens are summarized. Sex steroid hormones are an overlooked yet fundamental factor in oral homeostasis. They play important roles in the development and function of the periodontium, dental structure, mucosa and salivary glands. Dentists and healthcare providers should consider these hormonal factors when assessing and treating oral health conditions.